Multifunctional superparamagnetic nanoparticles conjugated with fluorescein-labeled designed ankyrin repeat protein as an efficient HER2-targeted probe in breast cancer. (December 2017) - Li, Dong-Li; Tan, Jian-Er; Tian, Ying; Huang, Shun; Sun, Peng-Hui; Wang, Meng; Han, Yan-Jiang; Li, Hong-Sheng; Wu, Hu-Bing; Zhang, Xing-Mei; Xu, Yi-Kai; Wang, Quan-Shi
Abstract: Based on the discordance of human epidermal growth factor receptor-2 (HER2) expression between primary and metastatic/recurrent breast cancer, HER2 molecular imaging, which had potential to systemically assess and dynamically monitor HER2 expression, might improve the selection of patients for anti-HER2 therapy. In this study, designed ankyrin repeat protein (DARPin) G3, a novel binding protein with picomolar affinity for HER2, was used and multifunctional superparamagnetic nanoparticles modified with fluorescein-5-maleimide-labeled DARPin G3 (SPIO-G3-5MF) were developed for HER2 imaging. Our results showed that SPIO-G3-5MF nanoparticles, which possessed uniform size of about 100 nm, favorable dispersity and low cytotoxicity, could selectively bind to HER2-positive breast cancer cells even in the presence of trastuzumab. Biodistribution assay demonstrated that abundant accumulation and long retention of SPIO-G3-5MF were observed in HER2-positive transplantation breast tumors although a portion of SPIO-G3-5MF nanoparticles were unavoidably captured by liver and spleen. Further MR imaging revealed that SPIO-G3-5MF could selectively image HER2-positive transplantation breast tumors, yielding remarkable T 2 signal reduction (50.33 ± 2.90% at 6 h and 47.29 ± 9.36% at 24 h). Our study suggested that SPIO-G3-5MF might be a promising MR molecular probe for diagnosing and monitoring HER2 expression state of breast cancer in the future. Highlights: Multifunctional nanoparticles (SPIO-G3-5MF) are successfully synthesized. SPIO-G3-5MF selectively and efficiently binds to HER2 in vitro and in vivo. SPIO-G3-5MF is capable of binding to HER2 even in the presence of Trastuzumab. SPIO-G3-5MF yields remarkable T 2 signal reduction in HER2-posivetive tumor in vivo. Long and effective tumor retention from 6 to 24 h post-injection was verified.